Effect of the Boron Concentration in Irrigation Water on the Elemental Composition of Edible Parts of Tomato, Green Bean, Potato, and Cabbage Grown on Soils With Different Textures - Rékási, Márk; Ragályi, Péter; Füzy, Anna; Uzinger, Nikolett; Dobosy, Péter; Záray, Gyula; Szűcs-Vásárhelyi, Nóra; Makó, András; Takács, Tünde (Frontiers in Plant Science, 2021)
The most important environmental source of boron (B) contamination is irrigation water. The data on the effect of B on the elemental composition in the edible parts of vegetables are scarce. A greenhouse pot experiment investigated the effect of irrigation water containing 0.1 and 0.5 mg/L B on the biomass, elemental (e.g., B, Mg, K, Fe, Cu, and Zn) composition, and photosynthetic parameters of tomato (Solanum lycopersicum), green bean (Phaseolus vulgaris), potato (Solanum tuberosum), and cabbage (Brassica oleracea) plants grown on 10 kg of sand, silty sand, or silty soil. The biomass of the edible part was unaffected by B treatment. The soil type determined the effect of B irrigation on the elemental composition of vegetables. The B content increased by 19% in tomatoes grown on silty soil. The 0.1 mg/L B treatment facilitated tomato fruit ripening on all soils, and the 0.5 mg/L B treatment doubled its chlorophyll content index (CCI) on silty soil. The 0.5 mg/L B treatment negatively affected the nutritional value of green beans on all soils, decreasing the Fe and K contents by an average of 83 and 34%, respectively. The elemental composition of potato was unaffected by the treatments, but the CCI of potato leaves increased in the 0.5 mg/L B treatment by 26%. The B content was increased by 39% in cabbages grown on light-textured soils. In conclusion, B concentration of up to 0.5 mg/L in irrigation water had no significant beneficial or adverse effect on the investigated vegetables, but 0.1 mg/L B treatment could shorten tomato fruit maturation time on B-poor soils. The B levels in vegetables remained suitable for human consumption.